Analysis of Patient Safety Culture to Improve Quality at Primaya Hospital Semarang - Aldrich Kurniawan Liemarto; Agatha Ferijani (Jurnal Indonesia Sosial Teknologi, 2025)
This study investigates patient safety culture in hospitals, highlighting its role in protecting patients from preventable harm through a culture of safety. Effective patient safety culture involves collaboration, open communication, and strong leadership support but faces challenges like resource limitations and inconsistent staff training. This study uses Primaya Hospital Semarang as a case example to examine how current safety practices align with quality improvement goals. A mixed-methods approach, including surveys and interviews with 169 staff members, used AHRQ’s safety culture survey to analyze teamwork, staffing, communication, and management support, identifying areas for targeted improvement. Key findings include that organizational learning and continuous improvement received the highest positive response (86.17%), followed by teamwork (83.43%) and communication about error (76.57%). However, staffing and work pace was notably weak, with only 48.08% positive responses. In interviews, a strong no-blame culture was emphasized for managing errors, although communication improvements were frequently suggested. Additionally, while routine error reporting was common, gaps in follow-up actions were noted, indicating areas for ongoing enhancement in patient safety practices.